Penentuan Pusat-pusat Kegiatan Baru sebagai Alternatif untuk Mengurangi Kemacetan Kota Bogor - Dewi Annisa Rizki; Ernan Rustiadi; Soekmana Soma (P4W LPPM IPB, 2017)
Bogor city is facing very serious congestion problems. Rearrangement of the spatial structure of the urban growth centers could improve the city's transportation system. This study aims to map the density of traffic, analyze the hierarchy of growth centers, analyze the spatial interactions and formulate alternative arrangement of the centers of the new activities. The study was conducted through descriptive analysis, Schallogram method, the Spatial Gravitation Model and TOPSIS. Schallogram analysis is used to analyze the hierarchy level of service. The Gravity Model is used to analyze the interaction between the regions. TOPSIS analysis is used to identify priority areas and new growth centers. This study analyzed data on the volume of vehicles, facilities area, population, road length, road network maps, and spatial plan (RTRW). The areas in the city center had the highest traffic density and the highest hierarchical. While suburban areas tend to have the lowest hierarchy. Based on the results of gravity model analysis, the areas with the highest attraction located in the city center and extends along the corridor to the north and the south. While the production area spread around the suburbs. Based on the analysis TOPSIS recommend new growth centers, namely Margajaya, Cimahpar, and Bojongkerta.